Novel agents for myelodysplastic syndromes. (December 2021) - Xu, Katie; Hansen, Elizabeth
Review objective: There have been several advances in the field of myelodysplastic syndromes over the past year, yielding two new US Food and Drug Administration drug approvals. The pharmacology, pharmacokinetics, clinical trials, therapeutic use, adverse effects, clinical use controversies, product description, and upcoming trials for myelodysplastic syndromes novel agents luspatercept-aamt and decitabine/cedazuridine are reviewed. Data sources: This review article utilized primary information obtained from both the published studies involved in the approval of luspatercept-aamt and decitabine/cedazuridine and package inserts for the respective medications. This review article utilized secondary information obtained from National Comprehensive Cancer Network guidelines using filters and keywords to sustain information relevancy as well as key studies using the keywords, "luspatercept-aamt, myelodysplastic syndromes, decitabine, cedazuridine, hypomethylating agent, ASTX727" from scholarly journal database PubMed. Data summary: Myelodysplastic syndromes consist of myeloid clonal hemopathies with a diverse range of presentation. Until recently, there have been relatively few new therapies in the myelodysplastic syndromes treatment landscape. On April 3, 2020 the US Food and Drug Administration approved Reblozyl ® (luspatercept-aamt), then on July 7, 2020, the US Food and Drug Administration approved INQOVI ® (decitabine and cedazuridine). Luspatercept-aamt acts as a erythroid maturation agent through differentiation of late-stage erythroid precursors. The safety and efficacy of luspatercept-aamt was demonstrated in the MEDALIST trial, a phase III trial in patients with very low-intermediate risk refractory myelodysplastic syndromes and ring sideroblasts. Luspatercept-aamt met both primary and secondary endpoints of transfusion independence of 8 weeks or longer and transfusion independence of 12 weeks or longer, respectively. Decitabine/cedazuridine has a unique mechanism of action in which decitabine acts as a nucleoside metabolic inhibitor promoting DNA hypomethylation and cedazuridine then prevents degradation of decitabine. The safety and efficacy of decitabine/cedazuridine was shown in the ASCERTAIN study, a phase III trial in patients with intermediate or high risk myelodysplastic syndromes or chronic myelomonocytic leukemia. The primary outcome evaluated was 5-day cumulative area under the curve between decitabine/cedazuridine and IV decitabine as well as additional outcomes including safety. Decitabine/cedazuridine met primary outcome and had a similar safety profile to IV decitabine. Conclusion: The novel myelodysplastic syndromes agents luspatercept-aamt and decitabine/cedazuridine provide a clinical benefit in the studied populations.